Digital health eco-systems: an epochal review of practice-oriented research - Stephanie, Lena (2023)
This article describes an epochal review of research literature on practice-oriented digital health ecosystems that have emerged during the period between 1998 and 2018. Practice-orientation refers to efforts that have resulted in positive impact and transformations in the delivery of healthcare. The review is epochal in the sense that there have been 3 major stages of innovation and diffusion in digital health that are identified. The year 1998 was deemed a significant starting point for the literature search because it marked the introduction of the term e-health. The main objective of this review is to track the evolution of digital health and the conspicuous developments in the field - crucial steps to get a grasp of the key issues involving the delivery of healthcare. The article includes a general discussion of these various key issues and sensitizing concepts. The sense-making thus shed some light on the areas of enquiry, which are central to identifying the direction in which the practice of healthcare is headed. These areas of enquiry often referred to as ‘substantive areas’ in qualitative research terminology, were identified as ‘electronic medical records’, ‘health cloud’, ‘data analytics’, ‘Internet-enabled devices’, and other ‘emerging information technologies’. The article concludes with a synthesis of key inferences drawn from the epochal review. The digital disruption of healthcare has created necessary conditions for its offering as a global, interoperable service.